2021
DOI: 10.1089/fpd.2020.2861
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Shiga-Toxin Producing Escherichia coli Carriage and Prevalence in the Ovine Meat Production Chain

Abstract: Shiga-toxin producing Escherichia coli (STEC) are zoonotic foodborne pathogens that are capable of causing serious human illness. Ovine ruminants are recognized as an important source of STEC and a notable contributor to contamination within the food industry. This review examined the prevalence of STEC in the ovine food production chain from farm-to-fork, reporting carriage in sheep herds, during abattoir processing, and in raw and ready-to-eat meats and meat products. Factors affecting the prevalence of STEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 195 publications
1
9
2
Order By: Relevance
“…Previous studies have reported prevalence in ovine, which were observed to be considerably variable between authors. McCarthy et al (2021) [ 28 ] calculated the relative prevalence of STEC in ovine feces from published data, which was established in 33.3% with ranges from 0.9% to 90.0%; according to this analysis, our prevalence results at 26.63% were similar. Despite the fact that we used a specific diagnosis route for STEC O157 detection, which included a selective enrichment, immunocromatography, and IMS, we were unable to detect STEC O157 in contrast to other authors [ 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies have reported prevalence in ovine, which were observed to be considerably variable between authors. McCarthy et al (2021) [ 28 ] calculated the relative prevalence of STEC in ovine feces from published data, which was established in 33.3% with ranges from 0.9% to 90.0%; according to this analysis, our prevalence results at 26.63% were similar. Despite the fact that we used a specific diagnosis route for STEC O157 detection, which included a selective enrichment, immunocromatography, and IMS, we were unable to detect STEC O157 in contrast to other authors [ 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 58%
“…"The diagnostic automation Enzyme-linked immunosorbent assay (ELISA) technique was used for the qualitative detection of E. coli 0157 antigens in all enriched samples" [22].…”
Section: Presumptive Identification Of Escherichia Coli 0157mentioning
confidence: 99%
“…More recently, feces of small domestic ruminants such as sheep and goats have emerged as important sources of E. coli O157:H7 implicated in human infections particularly with the widespread of petting farms and the increasing use of sheep and goats as major sources of meat [18][19][20][21][22][23]. However, information on this pathogen associated with small domestic ruminants in Nigeria still remain scanty and most often conducted in the Northern part of the country [21,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Domestic ruminants including cattle, sheep, and goats are the main reservoirs of STEC [ 2 , 3 , 4 , 5 ]. Ingestion of contaminated meat, dairy products, vegetables, and water is a risk factor for acquiring STEC infection in humans [ 2 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%